British Thoracic Society Quality Standards for acute non-invasive ventilation in adults. Issue 1 (5th April 2018) - Davies, Michael; Allen, Martin; Bentley, Andrew; Bourke, Stephen C; Creagh-Brown, Ben; D'Oliveiro, Rachel; Glossop, Alastair; Gray, Alasdair; Jacobs, Phillip; Mahadeva, Ravi; Moses, Rachael; Setchfield, Ian
Abstract : Introduction: The purpose of the quality standards document is to provide healthcare professionals, commissioners, service providers and patients with a guide to standards of care that should be met for the provision of acute non-invasive ventilation in adults together with measurable markers of good practice. Methods: Development of British Thoracic Society (BTS) Quality Standards follows the BTS process of quality standard production based on the National Institute for Health and Care Excellence process manual for the development of quality standards. Results: 6 quality statements have been developed, each describing a standard of care for the provision of acute non-invasive ventilation in the UK, together with measurable markers of good practice. Conclusion: BTS Quality Standards for acute non-invasive ventilation in adults form a key part of the range of supporting materials that the Society produces to assist in the dissemination and implementation of guideline's recommendations.